Income and Fiscal Incidence by Age and Gender: Some Evidence from New Zealand. (10th March 2015) - Aziz, Omar; Gemmell, Norman; Laws, Athene
Abstract : With many fiscal policies likely to have quite different age/gender incidences, this paper examines age and gender dimensions of income distribution and fiscal incidence in New Zealand using Household Economic Survey data for 2010. Applying, and testing, an intra‐household income sharing rule, our evidence suggests strong life‐cycle and gender aspects to fiscal incidence. Net tax liabilities are found to be low and negative, at younger and older ages but positive during much of the "working age." Notwithstanding considerable within‐gender heterogeneity, women are found on average to have systematically and persistently lower net fiscal liabilities than men, especially at older ages.